Around the world, adolescence is a time of heightened sensation seeking and immature self-regulation - Laurence Steinberg (2018)
© 2017 John Wiley & Sons Ltd The dual systems model of adolescent risk-taking portrays the period as one characterized by a combination of heightened sensation seeking and still-maturing self-regulation, but most tests of this model have been conducted in the United States or Western Europe. In the present study, these propositions are tested in an international sample of more than 5000 individuals between ages 10 and 30 years from 11 countries in Africa, Asia, Europe and the Americas, using a multi-method test battery that includes both self-report and performance-based measures of both constructs. Consistent with the dual systems model, sensation seeking increased between preadolescence and late adolescence, peaked at age 19, and declined thereafter, whereas self-regulation increased steadily from preadolescence into young adulthood, reaching a plateau between ages 23 and 26. Although there were some variations in the magnitude of the observed age trends, the developmental patterns were largely similar across countries.